Depression in Perimenopause and Postmenopausal Women - Falah Kadhim Khalaf; Hayder Sabah Saleh; Aysar Hashim Ali (Open Journal of Physicians and Surgeons, 2025)
Background: Menopause corresponds to a stage of life of the woman loaded with different connotations, generally of an involutive nature. This stage leads to an increase in the risk of numerous diseases, physical and cognitive impairment. Objective: To assess the Depression in perimenopause and postmenopausal women. Patients and methods: A prospective analytical cross-sectional study was conducted at our hospital, which included intentional non-probabilistic sample, of 212 patients in perimenopause or postmenopausal. Of the 212 patients evaluated, 73 were perimenopausal and 139 were postmenopausal. There were 70 patients with depression for a global frequency of 33%. Women with surgical menopause were excluded. Results: Among the perimenopausal the frequency of depression was 43.8% (32 patients), and among the postmenopausal, of 27.3% (38 patients) (χ2 = 9,636, P = 0.047). 65.6 % (21 cases) of the depressed perimenopausal patients, were classified as moderate, 25% (8 cases) as intermittent and 9.4% (3 cases) as severe. The distribution of postmenopausal patients was of 47.4% (18 women) moderate, 42.1% (16 cases) intermittent, 7.9% (3 cases) severe, and found a case in extreme category (2.6%). Conclusion: The frequency of depression is elevated (33%), higher in perimenopausal women than in the postmenopausal but is more severe in this last group, the risk factors for depression in the perimenopause are the degree of education and the symptoms vasomotors and in the postmenopause are the status marital and sexual activity.